2015
DOI: 10.12705/644.4
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitation in Orychophragmus (Brassicaceae) based on chloroplast and nuclear DNA barcodes

Abstract: Species delimitation is fundamental to the basic understanding of biodiversity because of the central role that the concept of species plays in most branches of biology. However, few studies have been designed to test conflicting delineations of plant species under an integrated species concept using DNA barcodes in combination with other lines of evidence. Such an approach may deliver more objective, testable and uniform species units as subjects for a range of studies. Here we aim to examine competing hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 61 publications
3
64
0
Order By: Relevance
“…An integrative practice using multiple criteria to circumscribe species boundaries will produce relatively objective and operational taxonomy (Su et al 2015, Hu et al 2015, Liu 2016; Lu et al 2017). In this study, we demonstrated that the Tibetan populations previously placed under C. monbeigiana or C. mollicoma should be erected as a distinct new species based on the following lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…An integrative practice using multiple criteria to circumscribe species boundaries will produce relatively objective and operational taxonomy (Su et al 2015, Hu et al 2015, Liu 2016; Lu et al 2017). In this study, we demonstrated that the Tibetan populations previously placed under C. monbeigiana or C. mollicoma should be erected as a distinct new species based on the following lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Its plants have been widely cultivated as ornamentals, vegetables, or source of seed oil (Sun et al, 2011). Despite controversial species delimitations in the genus (Zhou, 1987; Tan et al, 1998; Al-Shehbaz and Yang, 2000; Zhou et al, 2001; Wu and Zhao, 2003; Sun et al, 2012), our recent study based on nuclear (nr) ITS sequence variations suggested the recognition of seven species (Hu H. et al, 2015). Orychophragmus is sister to Sinalliaria , which is a genus endemic to China with one (Zhou et al, 2014) or two independent species (Hu H. et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Despite controversial species delimitations in the genus (Zhou, 1987; Tan et al, 1998; Al-Shehbaz and Yang, 2000; Zhou et al, 2001; Wu and Zhao, 2003; Sun et al, 2012), our recent study based on nuclear (nr) ITS sequence variations suggested the recognition of seven species (Hu H. et al, 2015). Orychophragmus is sister to Sinalliaria , which is a genus endemic to China with one (Zhou et al, 2014) or two independent species (Hu H. et al, 2015). Nuclear ITS sequence variations support the recognition of seven species and strongly resolve their interspecific relationships, but four DNA fragments ( mat K, rbc L, trn H- psb A, and trn L-F) of the chloroplast genome failed to do so (Hu H. et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations